2019
DOI: 10.1021/acssensors.9b00944
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Encoded Halide Sensor-Based Fluorescent Assay for Rapid Screening of Glutamate Transport and Inhibition

Abstract: Glutamate is the main excitatory neurotransmitter in the mammalian central nervous system. Excitatory amino acid transporters (EAATs) are a family of transmembrane transporters responsible for glutamate uptake into cells, and their malfunction is related to a variety of diseases, including neurodegenerative diseases and stroke. Screening for and developing inhibitors of EAATs as well as related transporters is a significant field of study for biomedical and pharmaceutical applications. Rapid, highthroughput me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…It is widely accepted that the abnormal neuronal activity of a seizure can induce excessive glutamate release, overactivation of the NMDA receptor, and then induce an increase in intracellular Ca 2+ , Na + , and Cl – levels, subsequently triggering a cascade of cellular responses including enhanced oxygen free radical production, disturbed mitochondrial function, cellular edema, and neuron damage. The level of ascorbate inside neuron is almost ten times larger than that in the interstitial fluid, and a series of studies have revealed that ascorbate concentration in the extracellular space might be modulated through glutamate–ascorbate heteroexchange, volume-sensitive anion channel activation, cellular edema, and neuron damage. From the results shown in Figure , we can see that neurons are damaged as reflected by largely decreased cell number, which might be a result of abnormal neuronal activity of seizure and in turn give rise to the increase of extracellular ascorbate concentration as revealed with our online sensing system. PE or infusion of MK-801 can suppress the neuron damage and maintain a significant population of neurons during seizure, as indicated by a much smaller increase in extracellular ascorbate.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is widely accepted that the abnormal neuronal activity of a seizure can induce excessive glutamate release, overactivation of the NMDA receptor, and then induce an increase in intracellular Ca 2+ , Na + , and Cl – levels, subsequently triggering a cascade of cellular responses including enhanced oxygen free radical production, disturbed mitochondrial function, cellular edema, and neuron damage. The level of ascorbate inside neuron is almost ten times larger than that in the interstitial fluid, and a series of studies have revealed that ascorbate concentration in the extracellular space might be modulated through glutamate–ascorbate heteroexchange, volume-sensitive anion channel activation, cellular edema, and neuron damage. From the results shown in Figure , we can see that neurons are damaged as reflected by largely decreased cell number, which might be a result of abnormal neuronal activity of seizure and in turn give rise to the increase of extracellular ascorbate concentration as revealed with our online sensing system. PE or infusion of MK-801 can suppress the neuron damage and maintain a significant population of neurons during seizure, as indicated by a much smaller increase in extracellular ascorbate.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Cells were incubated with prodrug for 0−180 min at 37 °C, 5% CO 2 , then removed from media and washed briefly with PBS. Cells were imaged as described previously 53 background subtraction. Images in Figure 2C were colored blue to represent the true fluorescent color of anthracene.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Cells were incubated with prodrug for 0−180 min at 37 °C, 5% CO 2 , then removed from media and washed briefly with PBS. Cells were imaged as described previously 53 using an inverted fluorescence microscope (Zeiss Axiovert 25), an X-Cite 120 light source (Spectra Services), a fluorescence filter set obtained from Omega Optical (XF02-2), and a Lumenera Infinity 3S-1URN microscope camera (Lumenera Corporation). Relative fluorescence intensity in cells was measured by using ImageJ software with background subtraction.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Another direct method, uptake of radiolabeled substrate by EAAT-expressing cells provides a rapid and sensitive readout of transporter function and inhibition ( Fontana, 2018 ), although the use and handling of radioactivity may be a drawback to use this method. Alternatively, indirect assays based on fluorescent probes and reporters such as membrane potential dyes ( Jensen and Bräuner-Osborne, 2004 ), glutamate sensors ( Armbruster et al, 2020 ), and intracellular anion sensors ( Zielewicz and Grewer, 2019 ) have proven successful to infer glutamate transport activity, although they require the introduction of non-physiological chemical labels. Recently, we reported on a label-free impedance-based method to assess activity and inhibition of nucleoside ( Vlachodimou et al, 2019 ), dopamine ( Sijben et al, 2021a ), and norepinephrine transporters ( Sijben et al, 2021b ) via activation of congruent G protein-coupled receptors (GPCRs) by their endogenous substrate in live cells, termed the TRACT assay.…”
Section: Introductionmentioning
confidence: 99%